Pengaruh Pembangunan Ekonomi Hijau Terhadap Kualitas Sumber Daya Manusia Di Indonesia - Gulo, Yupi Iman Berkat (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to examine the impact of hybrid work models on employee performance in the green economy era. This study aims to analyze how the transition to a green economy affects the quality of Human Resources (HR) in Indonesia. Using a literature approach and secondary data analysis, the study found that green development not only focuses on environmental sustainability but also creates new competency standards in the labor market. The results show that investment in the green sector is positively correlated with improved public health and the need for advanced technical education (upskilling).